Data Mining for Indonesian National Football team: Data mining for Indonesian National Football Team - Luki Ardiantoro; Ronny Makhfuddin Akbar; Yanuarini Nur Sukmaningtyas (Jurnal Mandiri IT, 2023)
The Indonesian national football team is controlled by the Indonesian Football Association, which is a member of FIFA and also a member of the AFC. The current coach of the Indonesian national team is Shin Tae-yong (STY), a former South Korean soccer player. In this study, the researcher intends to examine, study and obtain an overview of the game patterns, tactics and game strategies carried out by STY against the Indonesian national team. The goal to be achieved is gained of tactics and strategies for local coaches in the future. FP Growth algorithm was used for this research. Method to analyze match videos and record them in the form of statistical data in a set of data tupples (rows/records) for a particular match session was used. Then normalize the data, by forming a series of pattern numbers as a representation of the direction of attack in certain situation. The data set is formed with one set per round. As conclusion, data mining can be used to provide an overview of the national team's playing pattern. Thus, it makes it easier for coaches to determine the right strategy to beat opponents.